Expatriates’ boundary-spanning: double-edged effects in multinational enterprises - Liu, Ting; Sekiguchi, Tomoki; Qin, Jiayin; Shen, Ya Xi (Journal of International Business Studies, 2025)
Abstract Expatriates typically perform boundary-spanning to address challenges related to functional, linguistic, and cultural variations within multinational enterprises (MNEs), which in turn influences their relationships with host-country employees. Integrating social capital and role theory perspectives, this study explores the relational dynamics between expatriates and host-country employees by developing a novel theoretical framework that examines the double-edged effects of expatriates’ boundary-spanning. We propose that expatriates’ boundary-spanning nurtures mutual trust between expatriates and host-country employees, further facilitating expatriates’ identification with subsidiaries and host-country employees’ identification with MNEs. On the other hand, we propose that boundary-spanning increases expatriates’ role stressors, causing expatriates’ emotional exhaustion and outgroup categorization by host-country employees. We further categorize expatriates’ boundary-spanning into three types (functional, linguistic, and cultural) and theorize about their varying effects on the cognitive and affective bases of mutual trust and on role stressors. With data from 177 expatriate–host-country coworker dyads in Chinese MNEs, our double-edged framework is generally supported. Our findings suggest that cultural boundary-spanning exhibits the strongest double-edged effect, while functional boundary-spanning shows asymmetric effects, with negative outcomes surpassing positive ones, and linguistic boundary-spanning demonstrates the weakest effect. This study offers realistic and comprehensive insights into expatriates’ boundary-spanning, particularly in expatriate–host-country employee relationships.